Prospective Evaluation of Few Homeopathic Rubrics of Kent's Repertory From Bayesian Perspective. (October 2016) - Koley, Munmun; Saha, Subhranil; Das, Kaushik Deb; Roy, Sushabhan; Goenka, Rachna; Chowdhury, Pulak Roy; Hait, Himangsu; Bhattacharyya, Chapal Kanti; Sadhukhan, Sanjoy Kumar
Absolute grading system of homeopathic repertories poses substantial threat to reliability; however, it may be resolved by evaluating rubrics prospectively using likelihood ratio (LR). The authors evaluated few "physical general" rubrics from Kent's repertory—"chilly, " "hot, " "ambithermal, " "preference for hot/cold food, " "desire/aversion for fish/egg/meat/sour/pungent/salt/sweet/bitter"—prospectively in West Bengal, India, for 1.5 years using the Outcome Related to Impact on Daily Living scale. Per symptom/rubric, LRs < 1.5 were discarded. A total of 2039 encounters were analyzed for thermal relations and 4715 for desires/aversions for specific food items. Comparison with Kent's repertory revealed discrepancies. One new rubric with corresponding medicines was suggested to be introduced, new entries of medicines were recommended, and some seemed to maintain their ascribed importance. The authors refrained from converting LRs into typefaces prematurely; still they propose introducing LR to repertories for a structural update, changing its use, and enabling homeopaths to make more reliable predictions.